Streptomyces benahoarensis sp. nov. Isolated From a Lava Tube of La Palma, Canary Islands, Spain - Gonzalez-Pimentel, Jose L.; Hermosin, Bernardo; Saiz-Jimenez, Cesareo; Jurado, Valme (Frontiers in Microbiology, 2022)
Two Streptomyces strains, labeled as MZ03-37T and MZ03-48, were isolated from two different samples, a mucolite-type speleothem, and a microbial mat on the walls of a lava tube from La Palma Island (Canary Islands). Phylogenetic analysis based on concatenated sequences of six house-keeping genes indicated that both strains belonged to the same species. The closest relatives for both strains were Streptomyces palmae CMU-AB204T (98.71%), Streptomyces catenulae NRRL B-2342T (98.35%) and Streptomyces ramulosus NRRL B-2714T (98.35%). Multi-locus sequence analysis (MLSA), based on five house-keeping gene alleles (atpD, gyrB, recA, rpoB, trpB), indicated that both isolated strains were closely related to S. catenulae NRRL B-2342T. Whole genome average nucleotide identity (ANI) scores of both strains were in the threshold value for species delineation with closest species. Both strains presented a G+C content of 72.1 mol%. MZ03-37T was light brown in substrate and white in aerial mycelium, whereas MZ03-48 developed a black aerial and substrate mycelium. No pigment diffusion was observed in both strains. They grew at 10-37C (optimum 28-32C) and in presence of up to 15 % (w/v) NaCl. MZ03-37T grew at pH 5-10 (optimal 6-9) whereas MZ03-48 grew at pH 4-11 (optimal 5-10). LL-Diaminopimelic acid was the main diamino acid identified. The predominant fatty acids in both strains were iso-C16:0, anteiso-C15:0, C16:0 and iso-C14:0. The major isoprenoid quinones were MK-9(H6) and MK-9(H8), the main polar lipids were aminolipid, phospholipid and phosphoglycolipid. In silico analyses for functional annotation predicted the presence of gene clusters involved in resistome mechanisms and in the synthesis of described antimicrobials such as linocin-M18 and curamycin, as well as different genes likely involved in mechanisms for active compounds synthesis, both already described and not discovered so far. On the basis of their phylogenetic relatedness and their phenotypic and genotypic features, the strains MZ03-37T and MZ03-48 represented a novel species within the genus Streptomyces, for which the name Streptomyces benahoarensis sp. nov. is proposed. The type strain is MZ03-37T (= CECT 9805 = DSMZ 8002); and MZ03-48 (= CECT 9806 = DSMZ 8011) is a reference strain.